Design and Construction of a Chicken Egg Incubator. - Bwambale Edwin (Kabale University, 2023)
Due to the high demand for poultry products, artificial egg hatcheries should be used to increase the supply of poultry products. The backyard and small-scale poultry farmers are limited by the dependence on natural incubation or on commercial hatcheries for young birds for breeding. In this project an incandescent bulb heat source incubator is designed and constructed to hatch chicken eggs. The incubator system is an Arduino microcontroller-based that controls the heaters, and the mechanism for turning the tray. The temperature and the humidity in the incubator are displayed on a 16x2 LCD screen. The objective of the design is to help produce a low cost, energy efficient incubator for hatching chicken eggs.